Charge migration in photo-ionized aromatic amino acids. (20th May 2019) - Trabattoni, A.; Galli, M.; Lara-Astiaso, M.; Palacios, A.; Greenwood, J.; Tavernelli, I.; Decleva, P.; Nisoli, M.; Martín, F.; Calegari, F.
Abstract : Attosecond pump–probe spectroscopy is a unique tool for the direct observation of the light-activated electronic motion in molecules and it offers the possibility to capture the first instants of a chemical reaction. Recently, advances in attosecond technology allowed the charge migration processes to be revealed in biochemically relevant molecules. Although this purely electronic process might be key for a future chemistry at the electron time scale, the influence of this ultrafast charge flow on the reactivity of a molecule is still debated. In this work, we exploit extreme ultraviolet attosecond pulses to activate charge migration in two aromatic amino acids, namely phenylalanine and tryptophan. Advanced numerical calculations are performed to interpret the experimental data and to discuss the effects of the nuclear dynamics on the activated quantum coherences. By comparing the experimental results obtained in the two molecules, we show that the presence of different functional groups strongly affects the fragmentation pathways, as well as the charge rearrangement. The observed charge dynamics indeed present peculiar aspects, including characteristic periodicities and decoherence times. Numerical results indicate that, even for a very large molecule such as tryptophan, the quantum coherences can survive the nuclear dynamics for several femtoseconds. These results open new and important perspectives for a deeper understanding of the photo-induced charge dynamics, as a promising tool to control the reactivity of bio-relevant molecules via photo-excitation. This article is part of the theme issue 'Measurement of ultrafast electronic and structural dynamics with X-rays'.